PENGARUH MEDIA PEMBELAJARAN CROSSWORD PUZZLE TERHADAP HASIL BELAJAR IPS SISWA KELAS IV UPT SPF SDI GALANGAN KAPAL I KOTA MAKASSAR - Nurhalis; Muhammad Nawir, Syarifah Aeni Rahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The main problem in this study is how the influence of Crossword Puzzle learning media on the learning outcomes of fourth grade students of UPT SPF SDI Galangan Kapal I Makassar City. This study aims to determine the influence of Crossword Puzzle learning media on the learning outcomes of fourth grade students of UPT SPF SDI Galangan Kapal I Makassar City. This type of research is quantitative research with a Pre-Experimental research design in the form of One Group Pretest- Posttest research. The subjects in this study were 17 fourth grade students of UPT SPF SDI Galangan Kapal I Makassar City. The data collection technique used learning outcome tests and observation data. The collected data were analyzed quantitatively using descriptive statistics and inferential statistics. The results showed that the average pretest score was 52.59 and the posttest was 92.00. Based on the results of the Independent Samples Test hypothesis test, the sig. (2-tailed) value <0.05, which indicates that (H0) is rejected and (H1) is accepted. Data on the success of learning social studies using Crossword Puzzle learning media has increased, students are very enthusiastic about learning when using Crossword Puzzle media.